Neuropsychological phenotypes of 76 individuals with Joubert syndrome evaluated at a single center. Issue 7 (12th May 2017) - Summers, Angela C.; Snow, Joseph; Wiggs, Edythe; Liu, Alexander G.; Toro, Camilo; Poretti, Andrea; Zein, Wadih M.; Brooks, Brian P.; Parisi, Melissa A.; Inati, Sara; Doherty, Dan; Vemulapalli, Meghana; et al.
Abstract : Joubert syndrome (JS) is a genetically heterogeneous ciliopathy characterized by hypo‐dysplasia of the cerebellar vermis, a distinct hindbrain/midbrain malformation (molar tooth sign), and intellectual disability. We evaluated the neuropsychological profiles of 76 participants with JS in the context of molecular genetics and clinical covariates. Evaluations included neuropsychological testing, structured parental interviews, DNA sequencing, brain magnetic resonance imaging (MRI), electroencephalography (EEG), ophthalmologic examination, and assessment for renal and hepatic disease. On average, participants manifested Full Scale Intelligence Quotients (FSIQ) in the moderately to profoundly low range ( M  = 64.3 ± 15.3). Of the Wechsler index scores, verbal comprehension was least affected and processing speed was most affected. Receptive language was rated as better than expressive language on the Vineland Adaptive Behavior Scales‐Second Edition. Those with abnormal EEG had a significantly lower FSIQ ( n  = 15; M  = 50.7 ± 12.9) compared to participants with normal EEG ( n  = 39; M  = 64.7 ± 16.3; p  = .004). Participants taking psychiatric medications manifested a lower FSIQ ( n  = 20; M  = 54.8 ± 13.2) than those not taking them ( n  = 42; M  = 65.0 ± 17.2; p  = .022). These correlations were also present in the TMEM67‐related JS sub‐cohort ( n  = 14). Based on parental assessment, psychiatric and behavioral problems were significantly more common than in the general population for all measures ( p  < .004 for all). The majority (65%) of individuals with JS have some degree of intellectual disability. Abnormal EEG is associated with lower neuropsychological function. Processing speed is a weakness, while verbal comprehension and receptive language are relative strengths. These findings may guide parents, teachers, therapists, and doctors to determine appropriate therapies, accommodations, and academic goals for individuals with JS.